If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8x + -1 = 6x + -39 Reorder the terms: -1 + 8x = 6x + -39 Reorder the terms: -1 + 8x = -39 + 6x Solving -1 + 8x = -39 + 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. -1 + 8x + -6x = -39 + 6x + -6x Combine like terms: 8x + -6x = 2x -1 + 2x = -39 + 6x + -6x Combine like terms: 6x + -6x = 0 -1 + 2x = -39 + 0 -1 + 2x = -39 Add '1' to each side of the equation. -1 + 1 + 2x = -39 + 1 Combine like terms: -1 + 1 = 0 0 + 2x = -39 + 1 2x = -39 + 1 Combine like terms: -39 + 1 = -38 2x = -38 Divide each side by '2'. x = -19 Simplifying x = -19
| 4x+68=7x-13 | | 34-19=3(x-2) | | 40+5y-7=16y-12-2y | | x*6+115=x*15-11 | | 52=x+27 | | x+23+3x=-20-3x-27 | | 92-4x=14x+22 | | 9x^2=21x | | 2x+20=4x+6 | | x(3x-2)(x+6)= | | (3s-2)(4s+4)= | | 7x+32=x^2+4 | | 3.42/34.2 | | 3.42/24.2 | | 12=x/11 | | 8c*3v= | | -36x^2+96x-36=0 | | 2(5x+3)=4x-10 | | 1/6=6x | | 20x=460 | | 6=-3/5(4)+b | | 6=-3/5(4) | | -2x-6y=-74 | | 8x+3=6x+33 | | x+x+8+2x=240 | | 6x-(4x+3)=7 | | 6.3x=18.9 | | 9t^3+15t^2+t-6=t^2+t-6-3t^3 | | -12x^3+48x^2-36x=0 | | 8x+47=8(x+4) | | 7(4x-9)=40 | | 3x+6=-5-1x |